2014
DOI: 10.1021/ol502767m
|View full text |Cite
|
Sign up to set email alerts
|

Facile Formation of β-Hydroxyboronate Esters by a Cu-Catalyzed Diboration/Matteson Homologation Sequence

Abstract: The copper-catalyzed diboration of aldehydes was used in conjunction with the Matteson homologation, providing the efficient synthesis of β-hydroxyboronate esters. The oxygen-bound boronate ester was found to play a key role in mediating the homologation reaction, which was compared to the α-hydroxyboronate ester (isolated hydrolysis product). The synthetic utility of the diboration/homologation sequence was demonstrated through the oxidation of one product to provide a 1,2-diol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
(62 reference statements)
0
26
0
1
Order By: Relevance
“…! [37] Lastly, the propensity of 3 to form ate complexes was instrumental in increasing the nucleophilicity of the allylboronate and triggering as econd carbonyl addition. Thereaction with the heteroaromatic 3-benzothiophene aldehyde proceeded with excellent stereoselectivity (Table 1, entry 8), while 2-furaldehyde afforded the product with decreased optical purity (72 % ee,T able 1, entry 9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…! [37] Lastly, the propensity of 3 to form ate complexes was instrumental in increasing the nucleophilicity of the allylboronate and triggering as econd carbonyl addition. Thereaction with the heteroaromatic 3-benzothiophene aldehyde proceeded with excellent stereoselectivity (Table 1, entry 8), while 2-furaldehyde afforded the product with decreased optical purity (72 % ee,T able 1, entry 9).…”
mentioning
confidence: 99%
“…[35,36] In this instance,b oric ester 3 acts as an in situ protecting group for the secondary hydroxy group. [37] Lastly, the propensity of 3 to form ate complexes was instrumental in increasing the nucleophilicity of the allylboronate and triggering as econd carbonyl addition. [38] In this reaction, treatment with n-BuLi under Aggarwalsc onditions generated the ate complex, which collapsed to the borinic ester upon trapping of one labile alkoxy substituent with trifluoroacetic anhydride (TFAA).…”
mentioning
confidence: 99%
“…[7] Clark and co-workers conducted apioneering study of the catalytic borylation of ketones in 2010, and found that an achiral N-heterocyclic carbene (NHC)/copper(I) complex could be used to catalyze the diboration of various ketones to give the corresponding racemic tertiary a-hydroxyboronates in high yields. [8,9] However,t his work has not yet been extended to the development of an enantioselective process. [10,11] Herein, we report for the first time the enantioselective borylation of the aliphatic ketones 4 with 2 in the presence of ac hiral NHC/copper(I) complex catalyst to give the corresponding chiral tertiary a-hydroxyboronates 5 with moderate to high enantioselectivities (Scheme 1b).Ther esults of an extensive optimization study revealed that 1-cyclohexylethan-1-one (4a)r eacted with 2 (1.1 equiv) in THF at ambient temperature in the presence of CuCl (5 mol %) and an NHC salt, derived from trans-1-amino-2indanol (S,S)-L1 (5 mol %), [12] KOtBu (1.0 equiv), and MeOH (2.0 equiv) as ap roton source,t oa fford the corresponding chiral tertiary a-hydroxyboronate (S)-5a in good yield with high enantioselectivity (Table 1, entry 1).…”
mentioning
confidence: 99%
“…[7] Clark and co-workers conducted apioneering study of the catalytic borylation of ketones in 2010, and found that an achiral N-heterocyclic carbene (NHC)/copper(I) complex could be used to catalyze the diboration of various ketones to give the corresponding racemic tertiary a-hydroxyboronates in high yields. [8,9] However,t his work has not yet been extended to the development of an enantioselective process. [10,11] Herein, we report for the first time the enantioselective borylation of the aliphatic ketones 4 with 2 in the presence of ac hiral NHC/copper(I) complex catalyst to give the corresponding chiral tertiary a-hydroxyboronates 5 with moderate to high enantioselectivities (Scheme 1b).…”
mentioning
confidence: 99%
“…[6] For example,t ot he best of our knowledge,t here is only one example of catalytic enantioselective arylation of aliphatic ketones to give chiral tertiary alcohols with high enantioselectivity (> 80 % ee). [8,9] However,t his work has not yet been extended to the development of an enantioselective process. [8,9] However,t his work has not yet been extended to the development of an enantioselective process.…”
mentioning
confidence: 99%